(untitled) (Conferencea, 2024)
Geranium sanguineum (Bloody Cranesbill) is a medicinal herb traditionally used in treating various ailments such as gastrointestinal and skin diseases. This study reviews the chemical composition and pharmacological properties of Geranium sanguineum, focusing on its antioxidant, antimicrobial, anti-inflammatory, and anticancer activities. Key bioactive compounds include polyphenols, flavonoids, tannins, and essential oils. This review suggests the potential of Geranium sanguineum in therapeutic applications, although further studies, particularly clinical trials, are needed to establish its efficacy and safety in humans.